Motivasi dan Sikap Pencegahan Karies Gigi Pada Anak - Lilik Setiawan; Heru Suwardianto; Ni Putu Widari (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2021)
Abstract Dental and oral hygiene problems often occur in children aged 10-15 years. If left untreated, dental caries will cause inflammation of the nerves in the teeth which will make the teeth ache and can reduce the quality of life of a child. Purpose In this study was to analyze the relationship between motivation and attitudes to prevent dental caries in children aged 10-12 years in the village of Darungan Pare Kediri. Methods this study uses a descriptive correlation design with a cross sectional approach. The sampling method used was a total sample of 83 students who met the inclusion criteria with the data collection tool in the form of an online questionnaire. The results of the study on motivation and attitudes to prevent dental caries showed that of the 83 respondents with high motivation, 67 (80.7%) and 16 (19.3%) respondents who had moderate motivation and attitudes towards preventing dental caries showed good attitudes as many as 63 people. (75.9%) and respondents with moderate attitudes as many as 20 people (24.1%), The results of the Spearmean Rho P test <0.001, which means that Ha is accepted and the R value is 0.780. The correlation results in this hypothesis test fall into the category of strong correlation between the two variables. Conclusion. there is a relationship between motivation and attitudes to prevent dental caries in children. Suggestions increase children's knowledge and maintain good motivation and attitude related to the prevention of dental caries.. Keywords: Motivation, Attitude, Dental Caries